Pengembangan Formulasi Enteral Blenderized Tinggi BCAA Berbasis Bahan Pangan Lokal Labu Kuning, Tempe dan Ikan Gabus (LUTEKA) - Sari, Junjung Adita; Widyastuti, Endang Nur; Mustikaningrum, Fitriana (Universitas Tadulako, 2025)
Patient with liver cirrhosis experience metabolic changes in their bodies, including hypermetabolism and gluconeogenesis. These conditions lead to an increased need for nutrients, particularly albumin and Branched-Chain Amino Acids (BCAAs), which consist of isoleucine, leucine, and valine. Local foods can serve as raw materials for making enteral blenderized products for liver cirrhosis patients, such as tempeh and snakehead fish. This study aims to develop an enteral blenderized product, including formulation, viscosity testing, osmolality testing, flowability testing, sedimentation testing, and organoleptic testing, based on local foods like pumpkin, tempeh, and snakehead fish for liver cirrhosis. The study is an experimental research with two treatments, namely variations in the ratio of tempeh to snakehead fish, F1 (30:20) and F2 (25:25). Viscosity testing was conducted using a viscometer, osmolality testing with an Osmotech device, flowability testing with a 14 French catheter, sedimentation testing for 12 hours, and organoleptic testing using a 1–5 scale evaluated by 15 panelists. Viscosity analysis used the t-Independent test, and organoleptic test analysis used the Kruskal-Wallis test. There were differences in viscosity between F1 and F2 with a p-value < 0.05, osmolality of F2 was lower compared to F1, flowability of F2 was faster than F1, and F2 had no sedimentation after 3 hours. The results of the organoleptic test showed no difference between F1 and F2 with a p-value > 0.05. F2 is the selected formulation which is better than each test.